LCA of tall buildings: Still a long way to go. (September 2016) - Trabucco, Dario; Wood, Antony
Abstract: Tall buildings are often looked at as unsustainable, energy-voracious buildings. Although this may have been true in the past, modern tall buildings have to meet the same energy-conservation standards of all other buildings. In some cases, outstanding results have been obtained, which are now seen as the exemplary examples of sustainable design. Although the design and usage of buildings is now controlled by norms and codes, minimal studies have examined tall buildings holistically, from a life cycle perspective. The present paper analyzes the state-of-the-art of research on the life cycle assessment of tall buildings, analyzing the evolution of the discipline applied to this specific building type. Highlights: LCA is fundamental to understand the real "sustainability" of tall buildings. The complete understanding of a tall building LCA is still far away. LCA Research is missing for various components: Facades, HVAC, Foundations.